On Some Factors of Translation Multiplicity - Filippova, I.N. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
We analyze in the present paper the relationship between the correctness of the English and German linguistic cultures and the phenomenon of translation multiplicity. We point out national-linguistic and gender political correctness, realized in English language as feminization, androgenicity and the leveling of the gender marker, from strategy precisione gender in the German language. Comparing these trends with the modern Russian language we are proposing and trying to prove the thesis about the inevitability of the translation multiplicity (as text). We show non-identical versions of the translation texts which arise in the interaction of English, German and Russian languages (in various combinations). We identify optional text transformations in monolingual communication and the negative effects of racial and physiological effeminacy in intercultural and interlingual contacts in the fiction translation: a violation of the author's style, the devaluation of the storyline, discredit the author's text.